Interactions of TMPyP4 and TMPyP2 with Quadruplex DNA. Structural Basis for the Differential Effects on Telomerase Inhibition - Han, Frank Xiaoguang; Wheelhouse, Richard T; Hurley, Laurence H (Journal of the American Chemical Society, 1999)
The cationic porphyrins TMPyP4 and TMPyP2 possess similar structures but have strikingly different potencies for telomerase inhibition. To rationalize this difference, the interactions of TMPyP4 and TMPyP2 with an antiparallel quadruplex DNA were investigated. A single-stranded DNA oligonucleotide (G4A) containing four human telomere repeats of GGGTTA has been designed to form an intramolecular quadruplex DNA and was confirmed to form such a structure under 100 mM KCl by a DNA ligase assay, DMS footprinting, and CD spectrum analysis. By carrying out UV spectroscopic studies of the thermal melting profiles of G4A−porphyrin complexes, we provide evidence that TMPyP4 and TMPyP2 both stabilize quadruplex DNA to about the same extent. A photocleavage assay was used to determine the precise location for TMPyP4 and TMPyP2 in their interactions with quadruplex DNA. The results show that TMPyP4 binds to the intramolecular quadruplex DNA by stacking externally to the guanine tetrad at the GT step, while TMPyP2 binds predominantly to the same G4 DNA structure via external binding to the TTA loop. We propose that the inability of TMPyP2 to bind to the G4A by stacking externally to the guanine tetrad accounts for the differential effects on telomerase inhibition by TMPyP4 and TMPyP2.